Karakteristik Kimia Dan Organoleptik Biskuit Fungsional Dari Tepung Rumput Laut Dan Wortel Sebagai Pensubtitusi 30% Tepung Terigu - Nur Fadilah; Asriani Hasanudin; Minarny Gobel (Universitas Tadulako, 2019)
Biscuits are one of the most common snacks consumed by the community. The raw material for making biscuits is wheat flour. Efforts to reduce wheat imports and the use of wheat flour can be done by developing local products. Other ingredients that are often added in processed food products include seaweed and carrots. This study aims to determine the ratio of seaweed and carrot powder as a substance of substance 30% flour which produces good quality for consumption. Know the acceptance of panelists on the addition of seaweed and carrot starch as a substance 30% flour substitute on biscuits. This study used Completely Randomized Design (RAL) with 5 ratios (R: W) as treatment for substituting 30% wheat flour. The treatments were RW-1 (0: 0)%, RW-2 (4:26)%, RW-3 (6:24)%, RW-4 (8:22)%, RW-5 (10:20 )%. Each treatment was repeated 4 (four) times so that there were 4 x 5 = 20 experimental units. For organoleptic test using randomized block design (RAK) with 25 panelists as group. Chemical test parameters include carotene, fiber content, moisture content and organoleptic quality of color, aroma, taste, texture and overall fondness. The results showed that the ratio of seaweed flour and carrot starch produced the best quality was found in the RW-5 treatment because it has the highest fiber value of 14.176mg and the value of the proper water content based on the SNI that amounted to 4.56%, although having a low carotene amounted to 0.732mg. The best addition of seaweed flour and carrot flour was found in the RW-5 treatment where the values ​​of color, aroma and texture were acceptable to the panelists.